The readiness of Malaysian companies in the compliance of shariah requirements: Implication from the revised screening methodology - Ramli, Juliana Anis; Ramli, Mohd Ismail (2015)
This study attempts to examine whether the board facets could influence the Shariah-approved companies (ShACs)’ readiness in sustaining their Shariah status through the compliance of the Shariah requirements, following the Securities Commission (SC)’s revised screening methodology, and also to test whether there are significant differences in the Shariah compliance practices implication from the revised assessment. The data is gathered through a content analysis method which is taken from the corporate annual reports of the largest companies.On average, majority of the studied companies are competent to prevent themselves from being removed in the list of Shariah classification.Even though the minimum threshold of the SC’s revised screening assessments have been satisfied, however the companies’ Shariah compliance practices do not form any remarkable improvement especially after the revised takes place.The results seem to suggest that none the presence of majority Muslim directors, Muslim CEO and Muslim INEDs are able to exert significant influences on the readiness of ShACs in the compliance of Shariah through the quantitative assessments.However, the company size and industry type (control variables) have positive associations with the debt ratio benchmark.It is evident that different sector of industries has different inclination to adhere Shariah compliance through the SC’s debt ratio assessment.